Optimal path planning for intelligent automated wheelchair using DDSRPSO. Issue 1 (2nd November 2020) - Thirugnanasambandam, Kalaipriyan; R.S., Raghav; Loganathan, Jayakumar; Dumka, Ankur; V., Dhilipkumar
Abstract : Purpose: This paper aims to find the optimal path using directionally driven self-regulating particle swarm optimization (DDSRPSO) with high accuracy and minimal response time. Design/methodology/approach: This paper encompasses optimal path planning for automated wheelchair design using swarm intelligence algorithm DDSRPSO. Swarm intelligence is incorporated in optimization due to the cooperative behavior in it. Findings: The proposed work has been evaluated in three different regions and the comparison has been made with particle swarm optimization and self-regulating particle swarm optimization and proved that the optimal path with robustness is from the proposed algorithm. Originality/value: The performance metrics used for evaluation includes computational time, success rate and distance traveled.